Penarikan Kendaraan di Tengah Jalan Sebagai Cara Penyelesaian Wanprestasi di PT XXX Finance - M. Iqbal Abdurrahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Contractual relationships in the world of economics and business, usually involve an agreement between two parties, each party has obligations or achievements that must be fulfilled. If there is an imbalance in the fulfillment of obligations from one of the parties, default occurs. In this default case, the parties have entered into a murabahah financing contract, but because the debtor does not carry out his obligations to pay, the creditor makes a forced withdrawal by using the services of a third party with the intention of securing the financing object in the form of a car which will then be executed against the murabahah financing object. This research method is a qualitative method. The approach used is qualitative juridical, namely an analysis that bases or relies on legal reasoning, legal interpretation, and legal argumentation in a coherent and sequential manner, using theories, concepts, and legal principles obtained from the results of literature review. The conclusion in the dispute resolution by PT XXX Finance is not in accordance with legal procedures and has entered the realm of tort.